THE DEVELOPMENT OF A LEARNING MANAGEMENT MODEL INTEGRATING THE PHILOSOPHY OF SUFFICIENCY ECONOMY AND 21ST CENTURY LEARNING SKILLS TO PROMOTE DESIRABLE CHARACTERISTICS OF LEARNERS AT SAN SAI YAI RAK KINDERGARTEN SCHOOL, MUEANG KAEN PATTANA MUNICIPALITY, CHIANG MAI PROVINCE - Saninat, Natthaya (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to develop a learning management model by integrating the sufficiency economy philosophy and 21st Century learning skills for students at San Sai Yai Rak Kindergarten School, Muang Kaen Phatthana Municipality, Chiang Mai Province. This research utilized a mixed-methods approach and involved four research steps: Step 1: Research, which analyzed basic data for designing the learning management model. Step 2: Development, which designed and developed the learning management model. Step 3: Research, which implemented the learning management model. Step 4: Development, which evaluated and refined the learning management model. The research findings revealed that: 1) The individual development with the desired characteristics, practical concepts must be developed, namely, the concept of authentic learning management, the concept of self-directed learning, the concept of teacher empowerment, and the concept of integrated learning management. Key concepts related to the sufficiency economy philosophy and learning management. Integrating the sufficiency economy philosophy and 21st Century learning skills emphasized the principle that learning management skills could be developed. The result of this stage was the 4A1E Model, a framework developed and named by the researcher. 2) The 4A1E Model was the learning management model developed by this research. It integrated the sufficiency economy philosophy and 21st Century learning skills to foster desired student characteristics at San Sai Yai Rak Kindergarten. It consisted of 5 steps as follows: (1) raising awareness, (2) setting goals/development issues, (3) practicing/applying knowledge, (4) exchanging knowledge, and (5) evaluating. The development of this model was supported by various components, including workshops, practical teaching sessions that integrated the new philosophy, and continuous supervision, monitoring, and evaluation. 3) The study's results on the use of the new learning management model found that teachers' abilities on writing learning units, writing lesson plans, and organizing learning activities that successfully integrated the sufficiency economy philosophy and 21st Century learning skills were at a very good level. The teachers' opinions on the application of the philosophy of sufficiency economy and learning skills of learners in the 21st century learning skills were at the highest level. The students' desirable characteristics of sufficient living, after learning with the integrated model, were rated as excellent. Additionally, the students' opinions on the learning management approach were at a high level. 4) The results of evaluation of the learning management model, which integrated the Sufficiency Economy Philosophy and 21st century learner learning skills found that in terms of knowledge and understanding, practical skills, and sufficiency characteristics of learners, the results of evaluations from all evaluation sources showed that the average development results were at a higher rate.